THE FIELD INVESTIGATION OF SLIDING TRIGGERS OF SOIL MOVEMENT (LANSLIDS) USING THE GEOLISTRIC METHOD IN SAMBIREJO VILLAGE, PRAMBANAN DISTRICT, SLEMAN REGENCY: INVESTIGASI BIDANG GELINCIR PEMICU TANAH LONGSOR - agungprakosowicaksono, agung (ReTII, 2021)
Sambirejo Village, Prambanan District, Sleman District, Yogyakarta's Special Territory, as well as the most likely landslides disaster is high. This is evident in the multitude of incidents of motion on the ground, and it has resulted in the both physical and loss of life. The study was conducted to analyze ground-movement rock by means of a method of mapping surface geology and subsurface geological mapping. The mapping of surface geology provides insight into such as surfaces area litology, morphology, and geological structures. Sub-surface mapping of geology provides insight into the state of geology below the surface, such as lyric and geological structures. The research area have steep topography dominated by the sedimentary rock of a Tuff and Breksi Andesit and have high rainfall figures every beginning and end of the year. This study produced a subsurface 2D Geological modelling that was useful for investigating rocks from the trigger of soil motion. The existing type of soil movement is creep. Updated research can be used as of basic information on disaster mitigation, and regional building. Keywords: Sambirejo Village, Landslides, Tuff, Breksi Andesit.